Water quality, fish growth and rice plants growth in rice-fish recirculating integrated systems - Mohamad Nazirulzaman Bin Mohamad Saad (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Water is the main source for living things in daily life, thus, water quality especially from the waste product is important to be concerned. This research was focus on the water quality of the fish tank which consist of ammonia, nitrates and nitrites that were filtered by the filtration tanks. The filtration tanks were contain rice plants that were planted different planting density. The nitrates that contain inside the water from the fish tank were absorbed by the rice plants. Those contents and also temperature, dissolved oxygen, pH and nitrates were determined by using multi-parameter. The other data that has been measured were weight and length of the fish to observe the fish growth. The average final length and weight of the fish were 87.2 cm and 16.9 g respectively.The aim of the research study was to measure the water quality of the rice-fish recirculating integrated systems hence to improve the water quality by removing the nitrates and its effect to the fish and rice plants growth. Despite that, the nitrates produced were reused by the rice plants as the fertilizers for their growth. The growth of rice plants were determined by measuring the height of plants and number of tillers. At the end of this research the average number of tillers and height of rice plants for Treatment 1 were 12 and 95.8 cm while for Treatment 2, the average number of tillers was 19 and the average height of plants was 101.9 cm.